Neutrophil to lymphocyte ratio as a prognostic marker of deep neck space infections secondary to odontogenic infection. Issue 2 (February 2021) - Gallagher, N.; Collyer, J.; Bowe, C.M.
Abstract: Neutrophil to lymphocyte ratio (NLR) is a marker of infection and is used as a prognostic marker for cancer and cardiovascular disease. There is little application of NLR as a biomarker for odontogenic infection. C-reactive protein (CRP) is a commonly used marker for odontogenic infection that correlates with length of stay (LOS). The aim of this study was to assess the clinical utility of NLR as a prognostic marker of deep neck space infections secondary to odontogenic infection and to analyse its correlation with admission CRP and LOS. Data from January 2019 to December 2019 were retrospectively examined for patients admitted with a deep neck space infection of odontogenic cause. Data on admission CRP, NLR, sex, age, site of infection, LOS, treatment, ICU admission, and presence of comorbidities were analysed. A total of 161 patients were included, 89 (52.7%) of whom were male, and 72 (42.6%) female. Mean (SD) age was 38.4 (16.8) years (range: 5-86 years). Mean (SD) admission CRP and NLR were 105.9 (93.1) mg/L and 7.5 (7.7). Mean (SD) LOS was 2.9 (3.2) days (range: 0.5-35 days). Both admission CRP (p ≤ 0.01) and admission NLR (p ≤ 0.01). were significantly associated with LOS. Receiver operating characteristics analysis for LOS ≥ 2 days produced an area under the curve for CRP and NLR of 0.666 and 0.639. The optimum cut-off value of NLR for LOS ≥ 2 days was 4.65. In conclusion, NLR can be used as a prognostic marker for patients admitted with deep neck space infection secondary to odontogenic infection. Patients with NLR ≥ 4.65 are likely to require LOS ≥ 2 days.